2011
DOI: 10.1016/j.exger.2010.09.015
|View full text |Cite
|
Sign up to set email alerts
|

The lipid peroxidation products as possible markers of Alzheimer's disease in blood

Abstract: International audienceOxidative stress, which is present in Alzheimer's disease (AD), results in the formation of various end-products of free radical reactions with proteins and lipids. At present there are no reliable diagnostic biomarkers of AD in the blood. Therefore, specific products of lipid peroxidation in the blood of AD patients were investigated. Lipophilic extracts of erythrocytes in the group of patients with AD (n=44) and age-matched controls (n=16) were studied. The end-products of lipid peroxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 22 publications
2
31
0
2
Order By: Relevance
“…During oxidative stress and in many pathological events, enhanced levels of TBARS have been reported 3,5 . A study performed by Altuntas et al, on patients with schizophrenia reports an increased level of lipid peroxidation evidenced by enhanced MDA content 28 .Very recently Skoumalová et al show a significant increase in the end-products of lipid peroxidation, called lipofuscin-like pigments (LFP) in the red blood cells of Alzheimer's disease (AD) patients compared to controls 29 . Since at present there are no reliable diagnostic biomarkers of AD in the blood, to measure these specific products of lipid peroxidation in the red cells of AD patients may be a reliable marker of this pathological condition.…”
Section: Membrane Lipidsmentioning
confidence: 99%
“…During oxidative stress and in many pathological events, enhanced levels of TBARS have been reported 3,5 . A study performed by Altuntas et al, on patients with schizophrenia reports an increased level of lipid peroxidation evidenced by enhanced MDA content 28 .Very recently Skoumalová et al show a significant increase in the end-products of lipid peroxidation, called lipofuscin-like pigments (LFP) in the red blood cells of Alzheimer's disease (AD) patients compared to controls 29 . Since at present there are no reliable diagnostic biomarkers of AD in the blood, to measure these specific products of lipid peroxidation in the red cells of AD patients may be a reliable marker of this pathological condition.…”
Section: Membrane Lipidsmentioning
confidence: 99%
“…Erythrocytes do not have sufficient mechanisms to repair oxidized lipids in their membranes, which leads to the accumulation of these products in the membranes as well as inside the cell during the erythrocyte's lifespan. Fluorescence spectroscopy studies revealed the significantly increased level of lipid peroxidation specific products in erythrocytes and plasma of AD dementia and MCI patients [73,74]. These altered molecules could potentially be applied as biomarkers for detection of early AD.…”
Section: Aβ-induced Morphological Changes In Erythrocytesmentioning
confidence: 99%
“…13,14 AGEs increase the expression and activity of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase in human endothelial cells, an important source of vascular oxidative stress in Type 2 diabetes. 15 Increased NADPH oxidase activity results in formation of free radicals and depletion of cellular antioxidants such as glutathione, glutathione peroxidase, superoxide dismutase and catalase.…”
Section: 10mentioning
confidence: 99%